Disability Profile and Accessibility Limitations among Persons with Physical Disability in Nigeria - Chidozie Emmanuel Mbada; Oluwatoyin Olatoye; Funminiyi Olatoye; Clara Fatoye; Isaiah Adewale Oyewole; Kayode Israel Oke; Opeyemi Ayodiipo Idowu; Jamiu Opeyemi Yusuff; Daniel Oluwatimilehin Ibidunmoye; Francis Fatoye (The Center for Disability Studies and Services Brawijaya University, 2021)
Purpose: To evaluate disability profile and accessibility limitations among Persons Living with Disabilities (PLWDs) in Nigeria. Methods: 61 PLWDs (44 men, 17 women) consented for this study. World Health Organization Disability Assessment Schedule 2.0, Facilitators and Barriers Survey for People with Mobility Limitations version 2, Barthel Index, and Medical Expenditure Panel Survey Questionnaires were used to obtain data on physical disability profile, level of access barriers, activities of daily living and quality of access to health care respectively. A proforma was used to collect information on socio-demographic characteristics. Data were analyzed using descriptive and inferential statistics. Alpha level set at p< 0.05. Results: Prevalence of mobility, visual and hearing impairments were 60.7%, 21.3% and 6.6% respectively, There was a 11.5% rate of functional limitation while mild difficulty with cognition and life activities were reported among 96.7% and 65.6% of the respondents. 24.6% of the respondents had partial mobility dependence. There was low quality of access to health care (67.2%), high access barrier to home environment (73.8%) and transportation (93.4%). Conclusion: The PLWDs have high mobility impairment and face barriers in accessing healthcare, transportation and environment.